A framework for PM2.5 constituents-based (including PAHs) emission inventory and source toxicity for priority controls: A case study of Delhi, India. (September 2020) - Pathak, Ashutosh K.; Sharma, Mukesh; Nagar, Pavan K.
Abstract: A simple mass-based emission inventory (EI) of PM2.5 alone does not provide the information on the toxicity of the sources, as not all PM2.5 particles are equally toxic. The PM2.5 EI should have three inter-linked versions (i) mass-based, (ii) constituent-based and (iii) source toxicity-based. A framework (applied to the city of Delhi) to prepare constituent and source toxicity-based EI was developed. Mass emission of twelve sources was estimated for 89 constituents. The USEPA's CompTox database was used to estimate threshold concentration for the constituents of PM2.5 for carcinogenic, chronic and acute health effects. A product of mass emission of the constituent and inverse of its threshold concentration provides an assessment of toxicity of the source. Toxicity was not linearly associated with the mass emission. Road dust, vehicles, coal, dung, wood and coal power plant showed the highest toxicity as presence of metals Cr, Co, Cd, and As make these sources disproportionately more toxic. Among PAHs, Dibenzo (ah)anthracene, showed the highest cancer risk with its 98% emission from vehicles. The soft options replacing wood, crop, coal and dung with LPG, elimination of diesel power generation, burning of waste were simple and effective measures to reduce chronic toxicity by about 40%. Graphical abstract: Image 1 Highlights: Framework for speciated and source toxicity-based emission inventory. PM2.5 species like metals and PAHs determine toxicity of source. Toxicity of a source disproportionately higher than mass emission. New approach for prioritization of source control for health benefits.